Postconditioning with sevoflurane protects against focal cerebral ischemia and reperfusion injury involving mitochondrial ATP-dependent potassium channel and mitochondrial permeability transition pore. (January 2015) - Wang, Jun-Kuan; Wu, Hui-Fang; Zhou, Hui; Yang, Bo; Liu, Xian-Zhi
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: Postconditioning with sevoflurane has been shown to protect against focal cerebral ischemia and reperfusion injury. However, the mechanism remains elusive. In this study, we tested the hypothesis that mitochondrial ATP-sensitive potassium (mitoKATP) and mitochondrial permeability transition pore (mPTP) play roles in the neuroprotection of postconditioning with sevoflurane. Methods: Adult male Sprague-Dawley rats were subjected to MCAO for 90 minutes and then treated with sevoflurane at the beginning of reperfusion. The infarct volume, neurological deficit score, and brain edema were evaluated at 24 hours. Apoptosis were studied by TUNEL. The neuroprotective effect with or without 5-hydroxydecanoate (5-HD), a selective mitoKATP channel blocker or atractyloside (ATR), and an mPTP opener were analyzed. Results: Postconditioning with sevoflurane significantly decreased neurological deficit scores, infarct volume, and brain edema and also reduced apoptotic cells. 5-HD and ATR abolished the neuroprotective effect, respectively. 5-HD or ATR alone had no effect on ischemia and reperfusion injury. Discussion: Our data suggest that mitoKATP and mPTP play crucial roles in the neuroprotection of postconditioning with sevoflurane.